Preliminary results of the phylogenetic analysis of European hare (Lepus europaeus) - Mező, Blanka; Kusza, Szilvia (Acta Agraria Debreceniensis, 2014)
Brown hare (Lepus europaeus) is one of the most wide spread mammal in Europe. Its genetic structure is affected not only by last glacial, even by human activities (hunting, agricultural activities), isolation of such areas or competing for food resources. According to literature datas brown hare populations has different genetic variants in Europe, however its evolution, phylogenetics has not studied well. The main goal of this work was to know genetic structure of some brown hare. Mitochondrial DNA analysis was performed in two regions (D-loop, 513 bp and cytochrome-b, 1183 bp). Genetic distance values and Network analysis were calculated. NCBI Genbank was used for further sequences. Our results showed that Italian samples differed from the Genbank samples. We found two main clades: 1: Greece without islands; Bulgaria, Italy and Central-Europe; 2: East-Macedonia,Greece with islands, Cyprus and North Israel.